Comparative Study: Effectiveness of Marketing Campaigns in Traditional and Modern Retail - Wardatul Umayya Gea; Tuti Anggraini; Atika Atika (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
Digital transformation has changed consumer behavior in interacting and transacting with products and services, including in the retail sector. Consumers now tend to actively seek information and make purchases through digital platforms, encouraging modern retailers to adapt by utilizing social media, customer applications, and data-driven promotions. In contrast, traditional retailers still rely on conventional promotions and social proximity. This study aims to compare the effectiveness of marketing campaigns between traditional and modern retailers in Medan City. The method used was a qualitative comparative study approach. Data were collected through interviews, observations, and documentation, then analyzed using the SWOT technique with the IFAS and EFAS matrices. The results show that modern retailers are more effective in marketing campaigns because they are able to reach a wider market, customize promotions personally, and measure results in real time. Meanwhile, traditional retailers have advantages in customer loyalty and emotional connections, but have not yet optimally utilized technology. This study emphasizes the importance of traditional retailers to gradually integrate digital technology without abandoning the power of personal interactions, while modern retailers need to continue strengthening data-driven strategies to remain competitive.